Echogenic Technology Improves Cannula Visibility during Ultrasound-Guided Internal Jugular Vein Catheterization via a Transverse Approach - Konstantinos Stefanidis; Nicos Pentilas; Stavros Dimopoulos; Serafim Nanas; Richard H. Savel; Ariel L. Shiloh; John Poularas; Michel Slama; Dimitrios Karakitsos (Critical Care Research and Practice)
Objective. Echogenic technology has recently enhanced the ability of cannulas to be visualized during ultrasound-guided vascular access. We studied whether the use of an EC could improve visualization if compared with a nonechogenic vascular cannula (NEC) during real-time ultrasound-guided internal jugular vein (IJV) cannulation in the intensive care unit (ICU). Material and Methods. We prospectively enrolled 80 mechanically ventilated patients who required central venous access in a randomized study that was conducted in two medical-surgical ICUs. Forty patients underwent EC and 40 patients were randomized to NEC. The procedure was ultrasound-guided IJV cannulation via a transverse approach. Results. The EC group exhibited increased visibility as compared to the NEC group (88%  ± 8% versus 20%  ± 15%, resp. P<0.01). There was strong agreement between the procedure operators and independent observers (k=0.9; 95% confidence intervals assessed by bootstrap analysis = 0.87–0.95; P<0.01). Access time (5.2 s ± 2.5 versus 10.6 s ± 5.7) and mechanical complications were both decreased in the EC group compared to the NEC group (P<0.05). Conclusion. Echogenic technology significantly improved cannula visibility and decreased access time and mechanical complications during real-time ultrasound-guided IJV cannulation via a transverse approach.